Supplementation of sows with L-Arginine during gestating and lactation affects muscle traits of offspring related with postnatal growth and meat quality: From conception to consumption. (June 2019) - Oksbjerg, Niels; Krogh, Uffe; Jensen, Jens A.; Møller, Hanne S.; Ramaekers, Peter; Rasmussen, Martin Krøyer; Therkildsen, Margrethe; Theil, Peter K.
Abstract: This study investigated the effect of dietary inclusion of 25 g/day ofL -Arginine ( n  = 7) or iso‑nitrogenous amounts of alanine ( n  = 6) from d 30 of gestation to d 28 of lactation of sows on performance, muscle traits and meat quality in offspring. From each litter, heaviest and smallest littermate of both sexes were reared from d 28 and slaughtered at d 140 in accordance with a 2 3 factorial design. A response toL -Arginine were obtained on small females whereL -Arginine increased birth weight, however this effect disappeared at weaning.L -Arginine increased daily gain by 7% and increased the cross-sectional area of the M. semitendinosus in small females by 14%, suggesting an increased lean ratio. Mechanistic studies showed firstly, that small female littermates had increased number of muscle fibres (myogenesis) afterL -Arginine treatment (11%) and secondly increased total DNA (12%) as a consequence of satellite cell proliferation. Traits describing tenderness seem to be affected byL -Arginine but further studies are needed.